Sex differences in intestinal carbohydrate metabolism promote food intake and sperm maturation - Hudry,B; de,Goeij E; Mineo,A; Gaspar,P; Hadjieconomou,D; Studd,C; Mokochinski,J; Kramer,H; Plaçais,P-Y; Preat,T; Miguel-Aliaga,I (Cell, 2019)
Physiology and metabolism are often sexually dimorphic, but the underlying mechanisms remainincompletely understood. Here, we use the intestine of Drosophila melanogaster to investigate howgut-derived signals contribute to sex differences in whole-body physiology. We find thatcarbohydrate handling is male-biased in a specific portion of the intestine. In contrast to knownsexual dimorphisms in invertebrates, the sex differences in intestinal carbohydrate metabolism areextrinsically controlled by the adjacent male gonad, which activates JAK-STAT signalling inenterocytes within this intestinal portion. Sex reversal experiments establish roles for this malebiased intestinal metabolic state in controlling food intake and sperm production through gutderived citrate. Our work uncovers a male gonad-gut axis coupling diet and sperm production, andreveals that metabolic communication across organs is physiologically significant. The instructiverole of citrate in inter-organ communication may be significant in more biological contexts thanpreviously recognised.